Microalgae in health care and functional foods: β-glucan applications, innovations in drug delivery and synthetic biology - Chao Li; Chao Li; Chao Li; Ming Du; Yujie Han; Wentao Sun; Zixi Chen; Qiong Liu; Hui Zhu; Liqing Zhao; Shuangfei Li; Jiangxin Wang (Frontiers in Pharmacology)
Microalgae are emerging as a key player in healthcare, functional foods, and sustainable biotech due to their capacity to produce bioactive compounds like β-glucans, omega-3 fatty acids, and antioxidants in an eco-friendly manner. This review comprehensively discusses the role of microalgae in healthcare and functional foods, focusing particularly on β-glucan therapeutics, drug delivery innovations, and synthetic biology applications. In healthcare, microalgae-derived compounds show immense promise for treating diseases, boosting immunity, and tackling oxidative stress. Euglena-derived paramylon, a type of β-glucan, has shown potential in various medical applications, including immunomodulation and anticancer therapy. Synthetic biology and bioprocess engineering are enhancing microalgae’s therapeutic and nutritional value, with applications in drug delivery and personalized medicine. To maximize the potential of microalgae, further research and development are needed to address scalability, regulatory alignment, and consumer acceptance, with a focus on interdisciplinary collaboration and sustainable practices to align healthcare innovation with environmental conservation.